2022
DOI: 10.3390/biomedicines10061367
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biomarkers, Diagnostic and Therapeutic Approach in Rheumatoid Arthritis Interstitial Lung Disease—A Narrative Review

Abstract: Rheumatoid arthritis (RA) is considered a systemic inflammatory disease marked by polyarthritis which affects the joints symmetrically, leading to progressive damage of the bone structure and eventually joint deformity. Lung involvement is the most prevalent extra-articular feature of RA, affecting 10–60% of patients with this disease. In this review, we aim to discuss the patterns of RA interstitial lung disease (ILD), the molecular mechanisms involved in the pathogenesis of ILD in RA, and also the therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 113 publications
0
16
1
1
Order By: Relevance
“…One of the main reasons for mortality in RA patients, and the most common kind of lung involvement, is ILD 12 . Quality of life and likelihood of survival in patients with RA or other connective tissue diseases are significantly impacted by lung involvement, according to previous survival studies 19,20 . The theory behind treating RA‐ILD with glucocorticoids and immunosuppressants is that the early pathogenic feature of ILD is the invasion of inflammatory cells, which is followed by fibroblast proliferation and collagen deposition 21 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the main reasons for mortality in RA patients, and the most common kind of lung involvement, is ILD 12 . Quality of life and likelihood of survival in patients with RA or other connective tissue diseases are significantly impacted by lung involvement, according to previous survival studies 19,20 . The theory behind treating RA‐ILD with glucocorticoids and immunosuppressants is that the early pathogenic feature of ILD is the invasion of inflammatory cells, which is followed by fibroblast proliferation and collagen deposition 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations include interstitial lung disease, small airway disease, rheumatoid nodules, pleural effusion, pulmonary vasculitis, pulmonary fibrosis, etc (69). Although RA can involve many parts of the respiratory system, such as the airway or pleura, parenchymal lung involvement is associated with the highest morbidity and mortality (70). One diagnostic study showed that approximately 50% of RA patients had interstitial lung disease, of which only 10% had clinically significant symptoms such as cough and progressive exertional dyspnea (71), and that is because cytokine, chemotactic factor, and growth factor-mediated RA inflammatory process can promote FLS proliferation, increase the synthesis and deposition of extracellular matrix, and lead to pulmonary fibrosis (72,73).…”
Section: Treatment Of Ra-cvdmentioning
confidence: 99%
“…Kurasawa K. et al consider the titer of these antibodies as a marker of disease activity which can be used to evaluate the efficacy of the treatment [ 33 ]. The level of ferritin, C-reactive protein, Ro-52 antibodies and cutaneous vasculopathy also correlate with the severity of the disease and prognosis [ 5 , 20 , 44 , 61 , 62 , 63 ].…”
Section: Prognosismentioning
confidence: 99%